PEMBIASAAN PEDULI LINGKUNGAN SEBAGAI BENTUK PENGEMBANGAN KECERDASAN NATURALIS ANAK - Mawaddah, Elsy; Henny Helmi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to explain how cultivating environmentally conscious behavior can support the development of naturalistic intelligence in children aged 4–6 years through direct experiences in daily activities. Using qualitative descriptive methods, data were collected through observation, interviews, and documentation. The results show that simple activities such as caring for plants, utilizing used materials, maintaining the cleanliness of play areas, and observing the surrounding environment help children understand the relationship between human actions and natural conditions. These habits make children more sensitive to environmental changes, foster a sense of responsibility, and strengthen their ability to recognize natural patterns. These findings confirm that direct involvement in environmentally friendly activities significantly contributes to the growth of naturalistic intelligence in early childhood.